Exceptional case of Kasha's rule: Emission from higher-lying singlet electron excited states into ground states in coumarin-based biothiol sensing. (May 2018) - Hien, Nguyen Khoa; Nhan, Doan Thanh; Kim, Won Young; Van Bay, Mai; Nam, Pham Cam; Van, Dang Ung; Lim, In-Taek; Kim, Jong Seung; Quang, Duong Tuan
Abstract: A coumarin-based fluorescent sensor (7-Acryloxy-4-methylcoumarin, AMC ) for biothiols has been studied by a combination of quantum chemical calculation and experimental investigation. TheAMC selectively reacts with mercapto biomolecules via Michael addition, which can be served as a ratiometric fluorescent sensor for thiol-containing biomolecules. TheAMC sensor shows a selectivity towards biothiols with sensitivity in the order of cysteine > glutathione > homocysteine. Moreover, theAMC sensor can detect the cysteine concentration within the intracellular level. The results of the theoretical investigations on the electron excited states show that the lack of overlapping between MOs in transitions of the lower-lying singlet electron excited states and the small energy gap between electron excited states are the cause of fluorescence from the higher-lying singlet electron excited states, as an exception from Kasha's rule. The fluorescence from the higher-lying singlet electron excited states leads to marked fluorescence enhancement at long wavelength in the products of addition reaction of biothiols toAMC sensor. Graphical abstract: Highlights: A coumarin-derived ratiometric fluorescent sensor for the determination of biothiols via Michael addition was synthesized. Absorption and fluorescence characteristics were clarified on the basis of electronically excited states optimized geometries. The lack of overlap between MOs, and the small energy gap between electronically excited states lead to an exception of Kasha's rule.